Ephod – What Was It and What Was Its Use? A Question About the Potential Way Forward in the Development of Its Role in the Old Testament Texts - Lemański, Janusz (Verbum Vitae, 2024)
In biblical texts, ephod appears most often as part of priestly garb. In the statements of nonpriestly authors (before the Babylonian Exile), the linen ephod symbolizes priestly ministry in general. Sometimes, it is also regarded as an object of illicit worship (a practice condemned by the Deuteronomist) or an instrument necessary for divination practices (a symbol of priestly ministry). In these cases, the verb used indicates not so much a garment as an object. For the post-exile priestly authors, the richly woven and decorated ephod is henceforth exclusively part of the high priestly garb. This change in the role of the ephod represents the only discernible path of “evolution” in the use of ephod in the Hebrew Bible. One can only speculate about its possible earlier uses, such as garment put on statues of deities, based on the suggested (Akkadian, Ugaritic; cf. Isa 30:22) etymology of the word.